KEPASTIAN HUKUM PEMBAGIAN HARTA BERSAMA AKIBAT HILANGNYA SALAH SATU PASANGAN DALAM PERKAWINAN (Studi Komparatif Berdasarkan Hukum Perdata dan Kompilasi Hukum Islam) - Hamdani Hamdani (Jurnal At-Tabayyun, 2019)
The loss of a husband and wife certainly has legal consequences that must be sought for certainty in terms of marital status, the sharing of shared assets, or the distribution of inheritance. There is a significant debate between the Civil Code and the Compilation of Islamic Law related to how long it takes to determine the loss of a person and the distribution of shared property if the missing person is a husband or wife.This research is a descriptive analysis that leads to normative legal research, with a research approach to legal systematics. Data collection tool is obtained from secondary data, namely by means of literature study (library research). The data obtained were then analyzed using qualitative analysis. Based on the results of the study found that the determination of the legal status of missing persons based on the Civil Code in Article 467 of the Civil Code determines that someone who has left his residence within a period of 5 (five) years, or has passed 5 (five) years since the last clear clarity news about the condition of the person without authorizing to represent civil affairs and interests with the person to the Court to be summoned to appear before the court to ascertain their existence and fate and whereas according to Government Regulation Number 9 of 1975 Article 19 point (b) it is stated "one of the parties left another party for 2 years in a row without permission of another party without a valid reason or because of anything else beyond its ability. That the distribution of joint property due to the loss of one of the partners in the marriage in article 470 Burgelijk Wetboek (Civil Code), but with special conditions, namely if it has passed a period of 10 years and this is used as a basis for concluding that there is no appointment of someone to take care of their interests instead is a characteristic of the absence. The legal status of a missing person (mafqud) is considered dead. That the Determination of the Court Number: 0102 / Pdt.P / 2014 / PA.Btl has been in accordance with the theory of legal certainty namely orientation certainty, meaning that the law must be clear so that the public and judges can be guided by it.